VISIT THE BITING SITE IN LUMAJANG DISTRICT TO IMPROVE YOUR UNDERSTANDING OF ANCIENT INDONESIAN HISTORY: KUNJUNGI SITUS MENGGIGIT DI DISTRIK LUMAJANG UNTUK MENINGKATKAN PEMAHAMAN ANDA TENTANG SEJARAH INDONESIA KUNO - Rinna Rohmawati (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This writing aims to increase understanding of ancient Indonesian history, especially the Lamajang Tigang Juru Kingdom located in Lumajang, East Java, as a form of occupation that was the same era as the Majapahit Kingdom located in Trowulan, Mojokerjo. The big hope is that after understanding ancient history, we will grow in love and have a sense of pride in our country, Indonesia, which has been great since ancient times, the era of kingdoms with Hinduism and Buddhism, so that we will have a strong sense of nationalism because of its great history in the past. Indonesian historical events starting from prehistoric times, the Hindu Buddhist era or kingdoms, the era of colonialism to independence and reform until today. The history of Indonesia is uniquely beautiful and enchanting, so that the country of Indonesia is multicultural, consisting of various religions, traditions, customs and uniqueness. This is firmly engraved in a frame of diversity